Innovation Contests in Logistics - Birgit von See; Katharina Kalogerakis (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
Logistics is traditionally driven by operational demands. Therefore innovations are mainly based on direct customer requests. However, logistics service providers (LSPs) have started to realize the importance of proactive innovation to improve competitiveness. As they often lack internal competences and capacities, the open innovation paradigm (e.g. innovation contests) constitutes a promising way to improve their innovativeness. The aim of this paper is to evaluate the use of innovation contests as an open innovation initiative for LSPs. Opportunities and challenges for LSPs to conduct an innovation contest are analyzed. An in-depth case-study of the company Hermes, a German parcel distribution service provider that has successfully run an innovation contest, is used to derive success factors. Results indicate that LSPs can benefit from innovation contests, if they consider certain success factors. This study expands the discussion of open innovation to the logistics sector and supports LSPs in evaluating the potential of innovation contests for their business context.
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Innovation Contest; Logistics; Success Factors; Case Study